Highly accelerated real‐time cardiac cine MRI using k–t SPARSE‐SENSE. Issue 1 (6th August 2012) - Feng, Li; Srichai, Monvadi B.; Lim, Ruth P.; Harrison, Alexis; King, Wilson; Adluru, Ganesh; Dibella, Edward V. R.; Sodickson, Daniel K.; Otazo, Ricardo; Kim, Daniel
Abstract For patients with impaired breath‐hold capacity and/or arrhythmias, real‐time cine MRI may be more clinically useful than breath‐hold cine MRI. However, commercially available real‐time cine MRI methods using parallel imaging typically yield relatively poor spatio‐temporal resolution due to their low image acquisition speed. We sought to achieve relatively high spatial resolution (∼2.5 × 2.5 mm2) and temporal resolution (∼40 ms), to produce high‐quality real‐time cine MR images that could be applied clinically for wall motion assessment and measurement of left ventricular function. In this work, we present an eightfold accelerated real‐time cardiac cine MRI pulse sequence using a combination of compressed sensing and parallel imaging (k‐t SPARSE‐SENSE). Compared with reference, breath‐hold cine MRI, our eightfold accelerated real‐time cine MRI produced significantly worse qualitative grades (1–5 scale), but its image quality and temporal fidelity scores were above 3.0 (adequate) and artifacts and noise scores were below 3.0 (moderate), suggesting that acceptable diagnostic image quality can be achieved. Additionally, both eightfold accelerated real‐time cine and breath‐hold cine MRI yielded comparable left ventricular function measurements, with coefficient of variation <10% for left ventricular volumes. Our proposed eightfold accelerated real‐time cine MRI with k–t SPARSE‐SENSE is a promising modality for rapid imaging of myocardial function. J. Magn. Reson. Imaging 2013. © 2012 Wiley Periodicals, Inc.